Limited and idiosyncratic thermal acclimation in soil saprotrophic fungi - Maria Moreno-Druet; Anna Maria Kondrat; François Rineau; Nadejda A. Soudzilovskaia; Frederik De Laender (PLoS ONE, 2026)
Increased soil microbial activity due to higher temperatures caused by heatwaves could lead to higher carbon losses from soil into the atmosphere, further accelerating climate change. Hence, knowing how soil microbes respond to higher temperatures is crucial for improving soil-atmosphere carbon circulation models in the context of climate change. Thermal acclimation may reduce carbon losses from soils by retarding increases in microbial activity in response to elevated temperatures. However, the capacity of soil microbes to acclimate to realistic soil temperatures in vitro, and our ability to predict this acclimation based on traits, remains poorly understood. We tested how submission to two previous temperature treatments or ‘environmental histories’ affected subsequent growth at two exposure temperatures for seven widespread soil saprotrophic fungi. We hypothesized that (1) soil fungi have higher intrinsic growth and weaker self-limitation after exposure to a colder environmental history, and (2) the response of fungal eco-physiological traits (pigmentation and spore load) to elevated temperature exposure predicts fungal acclimation in terms of growth. Our results showed that environmental history had limited impact on the tested fungi, and trait responses to history temperatures did not predict fungal growth after treatment with both history and exposure temperatures. We conclude that fungal thermal acclimation is limited and idiosyncratic.